Effect of Rosiglitazone on Common Carotid Intima-Media Thickness Progression in Coronary Artery Disease Patients Without Diabetes Mellitus - Sidhu, Jagdip S.; Kaposzta, Zoltan; Markus, Hugh S.; Kaski, Juan Carlos (Arteriosclerosis, thrombosis, and vascular biology, 2004)
Objectives— Thiazolidinediones, such as rosiglitazone, have been shown to retard atherosclerosis disease progression in diabetic subjects. These agents may have anti-atherosclerotic effects through direct inhibition of inflammatory processes in the vessel wall, and so their benefit may extend to patients with atherosclerotic disease, even in the absence of diabetes. In this study, we assessed the effect of rosiglitazone on common carotid intima-media thickness (IMT) progression in nondiabetic coronary artery disease (CAD) patients. Methods and Results— Consecutive subjects (n=92) with clinically stable, angiographically documented CAD and without diabetes mellitus were randomized in a double-blind manner to receive placebo or rosiglitazone for 48 weeks. They received single-dose placebo and rosiglitazone 4 mg daily for the initial 8 weeks, and the doses were doubled for the remainder of the study. Common carotid IMT together with fasting glucose, insulin, and lipid profile were measured at baseline and repeated after 24 and 48 weeks. Rosiglitazone-treated patients showed reduced IMT progression compared with the placebo group, −0.012 mm/48 weeks versus 0.031 mm/48 weeks ( P =0.03). Rosiglitazone treatment significantly reduced insulin resistance, estimated by homeostasis model of insulin resistance index, compared with placebo ( P =0.01). Conclusions— Rosiglitazone reduces common carotid IMT progression in nondiabetic CAD patients, and insulin-sensitization may be one contributory mechanism.